The effects of non-tariff barriers on trade pattern of Sarawak shrimp industry - Pada, ak. Bijo. (2004)
This research paper seeks to assess the effects of non-tariff barriers on trade pattern of Sarawak shrimp industry in term of quantity, value and destination of shrimp export from 1991 until 2002. Non-tariff barriers are any other measures other than tariff that could restrict international trade flow.